2023
DOI: 10.1002/jobm.202200632
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal potential of different size sericin‐capped silver nanoparticles synthesized by heat, light, and sonication

Abstract: Present study was aimed to assess the bactericidal potential of sericin‐capped silver nanoparticles (Se‐AgNPs) synthesized by heat, light, and sonication. Se‐AgNPs were characterized by size analyzer, UV spectrophotometry, energy‐dispersive X‐ray spectroscopy, and Fourier transform infrared spectroscopy. Average size of Se‐AgNPs synthesized by heat, light and sonication was 53.60, 78.12, and 7.49 nm, respectively. All (10) bacterial strains were exposed to Se‐AgNPs prepared from different methods to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 80 publications
(120 reference statements)
6
7
0
Order By: Relevance
“…(2023) and Subhani et al . (2023) also reported the shifting of the color of the solution when added with natural reducing agents or phytosubstances [45–47] . Following the UV–vis spectral study, the peak was also found at 425 nm which authenticated the fabrication of AgNPs.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…(2023) and Subhani et al . (2023) also reported the shifting of the color of the solution when added with natural reducing agents or phytosubstances [45–47] . Following the UV–vis spectral study, the peak was also found at 425 nm which authenticated the fabrication of AgNPs.…”
Section: Discussionmentioning
confidence: 89%
“…(2019) demonstrated that the bioactivity of AgNPs depends on various properties such as charges, morphology, and surface plasmon resonance [57] . The polydispersity index of the prepared NPs was found less than 0.5 which is a confirmation of the normal small size distribution of the NPs for significant bactericidal activity [46] . According to previous reports, the main integrated peaks 27.79°, 32.08°, 45.88°, 56.88, and 66.50° of XRD diffractogram at 2 θ values were observed [58] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Using ultrasonic homogenizer/sonicator (CY‐500), Se‐AgNPs were manufactured by administering the analytical‐grade silver nitrate (AgNO 3 , Sigma Aldrich, Germany, purity: 99.3%) with sericin in 1:2.5 (40 mg silver/100 mL of sericin 0.15%/15 mg) at 40°C for 1 h with pulse rate of (15:05) and intensity of 90 (Summer et al, 2023). After the optimum exposure to the ultrasound waves, color of the solution was converted from colorless to dark brown.…”
Section: Methodsmentioning
confidence: 99%
“…Different effects can be caused by physically or chemically synthesized AgNPs including DNA damage, developmental abnormalities, variation in the gene expression, and disturbance of the metabolism depending on concentration. The toxicity of AgNPs varies significantly depending on the shape, size, exposure pathway, and capping agents [ 22 ].…”
Section: Introductionmentioning
confidence: 99%